Long-Term Incidence of Atrial Fibrillation and Stroke Among Cross-Country Skiers: Cohort Study of Endurance-Trained Male and Female Athletes. Issue 11 (10th September 2019) - Svedberg, Niclas; Sundström, Johan; James, Stefan; Hållmarker, Ulf; Hambraeus, Kristina; Andersen, Kasper
Abstract : Background: Studies have revealed a higher incidence of atrial fibrillation among well-trained athletes. We aim to investigate associations of endurance training with incidence of atrial fibrillation and stroke and to establish potential sex differences of such associations in a cohort of endurance trained athletes. Methods: All Swedish skiers (208 654) completing 1 or more races in the 30 to 90 km cross-country skiing event Vasaloppet (1989–2011) and a matched sample (n=527 448) of nonskiers were followed until first event of atrial fibrillation or stroke. Cox regression was used to investigate associations of number of completed races and finishing time with incidence of atrial fibrillation and stroke. Results: Female skiers in Vasaloppet had a lower incidence of atrial fibrillation than did female nonskiers (hazard ratio [HR], 0.55; 95% CI, 0.48–0.64), independent of finishing time and number of races. Male skiers had a similar incidence to that of nonskiers (HR, 0.98; 95% CI, 0.93–1.03). Skiers with the highest number of races or fastest finishing times had the highest incidence. Skiers of either sex had a lower incidence of stroke than did nonskiers (HR, 0.64; 95% CI, 0.60–0.67), independent of the number of races and finishing time. Skiers with atrial fibrillation had higher incidence of stroke than did skiers and nonskiers without atrial fibrillation (men: HR, 2.28; 95% CI, 1.93–2.70; women: HR, 3.51; 95% CI, 2.17–5.68; skiers with atrial fibrillation vs. skiers without atrial fibrillation). After diagnosis of atrial fibrillation, skiers with atrial fibrillation had a lower incidence of stroke (HR, 0.73; 95% CI, 0.50–0.91) and lower mortality compared with nonskiers with atrial fibrillation (HR, 0.57; 95% CI, 0.49–0.65). Conclusions: Female skiers in Vasaloppet had lower incidence of atrial fibrillation and stroke. Male skiers had similar incidence of atrial fibrillation and lower risk of stroke. Men with higher number of races and faster finishing times had the highest incidence of atrial fibrillation. After diagnosis of atrial fibrillation, skiers had lower incidence of stroke and death than did nonskiers with atrial fibrillation. This indicates that although on an individual level atrial fibrillation in well-trained individuals is associated with higher incidence of stroke, on population level, risk of stroke is low and that exercise should not be avoided. Abstract : Supplemental Digital Content is available in the text.